2014
DOI: 10.5505/tjtes.2014.71597
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Prognosis of Penetrating Eye Injuries in Geriatric Patients in the Southeastern Region of Anatolia Turkey

Abstract: BACKGROUND:The purpose of this study was to evaluate the etiologic and prognostic factors of open eye injuries in geriatric patients in the Southeastern region of Anatolia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…12 Higher rates of wood OGIs have been described in rural settings and foreign countries and are ascribed to the predominance of agriculture in these regions. 3,4,13 It was anticipated that there would be a significantly higher rate of IOFBs caused by wood because of its tendency to fragment in orbital injuries, necessitating multiple periorbital 14,18 We also observed that there was no significant difference in endophthalmitis between patients injured by plant or EW materials, but our study might have been underpowered to detect a true difference. Regardless, the porous nature of wood allows for transport of soil contaminant, which has been associated with increased risk.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…12 Higher rates of wood OGIs have been described in rural settings and foreign countries and are ascribed to the predominance of agriculture in these regions. 3,4,13 It was anticipated that there would be a significantly higher rate of IOFBs caused by wood because of its tendency to fragment in orbital injuries, necessitating multiple periorbital 14,18 We also observed that there was no significant difference in endophthalmitis between patients injured by plant or EW materials, but our study might have been underpowered to detect a true difference. Regardless, the porous nature of wood allows for transport of soil contaminant, which has been associated with increased risk.…”
Section: Discussionmentioning
confidence: 67%
“…12 Higher rates of wood OGIs have been described in rural settings and foreign countries and are ascribed to the predominance of agriculture in these regions. 3,4,13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Among geriatric patients, wood strike was the most common reason for penetrating eye trauma in Turkey. 7 Wooden material causing eye and intraorbital injuries have varied from branches and sticks to pencils, bamboo sticks, and corn stalks in previous studies. 4,[8][9][10] As an organic material, untreated wood entails a risk for serious infections.…”
Section: Introductionmentioning
confidence: 99%
“…4 -6 Among geriatric patients, wood strike was the most common reason for penetrating eye trauma in Turkey. 7…”
Section: Introductionmentioning
confidence: 99%